Artificial Intelligence and the Complexity of Ethics - Kirchschlaeger, Peter G. (Asian Horizons, 2024)
While reflecting upon artificial intelligence, one of its characteristics is often highlighted: its complexity. Sometimes the complexity of artificial intelligence is even used as an argument against holding humans responsible for it. At the same time, surprisingly the complexity of ethics is usually perceived with a reductionist understanding of ethics. In this article, the concept “artificial intelligence” itself is critically reviewed resulting in the introduction of a more adequate term: “databased systems.” Beyond that, I argue against the possibility of “ethical” databased systems and in favour of databased systems with ethics. Finally, the complexity of ethics and its consequences for the ethical dimension of technology-based innovation will be in the focus.